In situ integrated tuner approach for load‐pull measurement of Si/SiGe:C HBT at 200 GHz. Issue 15 (1st July 2014) - Hasnaoui, I.; Pottrain, A.; Lacave, T.; Chevalier, P.; Gloria, D.; Gaquiere, C.
Abstract : Load impedance variations were obtained using an innovative integrated tuner at G‐band. The 200 GHz load‐pull measurements on a silicon–germanium (SiGe) heterojunction bipolar transistor (HBT) are presented. First, the linearity of the integrated tuner is checked. Then, the main load‐pull characteristics are extracted from a 0.13 × 3 µm 2 emitter area SiGe HBT. The aim of this study is to provide a solution to avoid losses related to probes and commercial tuners. Thereby, from design to measurements, power setup architecture, calibration and performances at 200 GHz are performed in a non‐50 Ω environment. Finally, comparisons between measurements and simulation from a high current model (HICUM) show good agreement, demonstrating the capability of the measurement approach.